A new variety of peas ‘Altaysky Universalny’ - S. K. Shchukis; E. R. Shchukis (Зерновое хозяйство России)
Nowadays the problem of production of high qualitative and natural plant protein is of great importance. Leguminous plants are one of the main sources of protein, in Russia it is peas. Peas have a great economic value due to its variety of application and its unique biochemical composition. Thus the improvement of its breeding is of great and urgent importance. The Altay Area with its large territory, well defined zoning and changeable climate needs a great range of different, complementary and stress tolerant varieties. FSBSI ‘Altay RIA’ has been conducting a purposeful breeding work with leguminous plants since 1970. During the period the institute developed seven varieties of peas. In 2014 a new leafy variety of peas ‘Altaysky Universalny’ was listed into the State List (Register) of Breeding Achievements, approved for use in the West-Siberian region (24.01.2012. B№174. RU №6453 of 04.05.2012). The variety of peas ‘Altaysky Universalny’ is a middle maturing variety. The resistance to lodging, seed cracking and fall is the same as of the standard variety. The drought tolerance is above average. The resistance to diseases and pests is the same as of the standard variety. The variety combines forage and grain productivity. Grain productivity during the years of Variety Testing (2009-2011) was 1.99 t/ha, that is on 0.25 t/ha more than that of the standard variety. 1000-seed weight is 230 g, that is on 25 g more than that of the standard variety. The content of raw protein in absolutely dry matter is 21.5-23.6%. It’s necessary to note, the new variety of peas ‘Altaysky Universalny’ possesses a number of valuable economic and biological traits and properties, which can be used in the breeding process. Its wide application on the farms of the West-Siberian region will improve food and forage background as well as solve a key problem of biological agriculture.